2019
DOI: 10.1089/hum.2018.059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MicroRNA-9-5p Protects Against Cardiac Remodeling Following Myocardial Infarction in Mice

Abstract: Follistatin-like 1 (Fstl1) protects cardiomyocytes from a broad spectrum of pathologic injuries including myocardial infarction (MI). It is worthy of note that although cardiac Fstl1 is elevated in post-MI microenvironment, its cardioprotective role is still restricted to a limited extent considering the frequency and severity of adverse cardiac remodeling following MI. We therefore propose that intrinsic Fstl1-suppressing microRNA (miRNA) may exist in the heart and its neutralization may further facilitate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…Once addressed the induction of FSTL1 in TGF β1-mediated EMT of EMCs, we investigated whether FSTL1 could be a direct target of miR-200c. Several studies already demonstrated the presence of multiple miRNA-binding sites in the 3′UTR of FSTL1 mRNA and their role in the inhibition of FSTL1 expression [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once addressed the induction of FSTL1 in TGF β1-mediated EMT of EMCs, we investigated whether FSTL1 could be a direct target of miR-200c. Several studies already demonstrated the presence of multiple miRNA-binding sites in the 3′UTR of FSTL1 mRNA and their role in the inhibition of FSTL1 expression [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…miR-9-5p may exert a cell-specific effect during cardiac fibrosis. Inhibition of miR-9-5p in cardiomyocytes reverses cardiac remodeling (Xiao et al, 2019) while it suppresses CF activation (Fierro-Fernandez et al, 2015;Wang et al, 2016). Its effect on CF seems plausible because it targets TGFBI, which is expressed predominately in fibroblasts (Uhlen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression level of miR-9 was upregulated in H9C2 cells subject to hypoxia, and the hypoxia-induced cardiomyocyte apoptosis was inhabited by the miR-9 knockdown procedure [ 28 ]. The expression level of miR-9-5p decreased in the ischemic myocardium [ 29 ]. Jin et al established the rodent myocardial infarction model and proved that compared with the sham group, the rats in the miR-9 group had substantially decreased type I and type III collagen, suggesting that miR-9 can alleviate the myocardium fibrosis process in cardiomyopathy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%